Incidence, timing and risk factors of venous thromboembolic events in patients with pancreatic cancer. Issue 207 (November 2021) - Hanna-Sawires, Randa G.; Groen, Jesse V.; Hamming, Alexander; Tollenaar, Rob A.E.M.; Mesker, Wilma E.; Luelmo, Saskia A.C.; Vahrmeijer, Alexander L.; Bonsing, Bert A.; Versteeg, Henri H.; Klok, F.A.; Mieog, J.Sven D.
Abstract: Introduction: Pancreatic cancer is associated with a high risk of venous thromboembolism (VTE). However, comprehensive data on incidence, timing and relevant determinants of VTE in this particular population are scarce. Current study assesses incidence, timing and predictors of VTE in pancreatic cancer through different phases of disease. Methods: All pancreatic cancer patients treated in our tertiary referral center between 2013 through 2017 were studied. Occurrence of VTE was evaluated from diagnosis through end of follow-up or death. Relevant determinants of VTE were identified in logistic regression models. Hazard ratios were calculated to evaluate impact of VTE on overall survival. Results: In total, 361 patients were followed for a median period of 43 months; 64 were diagnosed with VTE (18%). Most were tumor related thrombosis (59%), incidental (75%) and occurred after anti-cancer treatment had been stopped (80%), only 1.6% occurred during remission phase. Stage IV pancreatic cancer was a predictor for VTE (hazard ratio (HR) 2.46, 95% confidence interval (CI) 0.9–6.8). Biliary drainage (HR 0.52, 95%CI 0.28–0.98) and tumor resection (HR 0.45, 95%CI 0.45–1.83) were protective factors. VTE was not associated with worse survival (HR 1.3; 95% CI 0.97–1.74). Conclusions: VTE in pancreatic cancer is disease-stage dependent, with 80% occurring in advanced phases of disease when patients no longer receive active treatment. We speculate that this is the main reason for the absence of a survival effect of VTE in our cohort. These practice-based findings should be taken into account when considering wide-spread introduction of primary thromboprophylaxis in patients with pancreatic cancer. Highlights: 'What is known on this topic' Pancreatic cancer is among the most prothrombotic malignancies There are ongoing discussions on the introduction of prophylactic anticoagulation in cancer patients 'What does this paper add' A detailed overview of different types of VTE in all stages of pancreatic cancer Tumor location, age and stage are predictors for development of VTE 80% of all VTE occurs in the advanced disease phase. It is therefore debatable whether prophylactic anticoagulation is beneficial for this patient population